The Design of a Smart Intelligent Device for Visually Handicapped - Smita Francis; Sicilia Mutilifa (Current Overview on Science and Technology Research Vol. 10, 2022)
The World Health Organisation reports that 4% of the world’s population is visually impaired and 90% of the visually impaired live in low-income settings. This paper presents an intelligent low-cost device to enhance the mobility of the visually handicapped user and track the user in real-time. The proposed device will assist in the mobility of the visually impaired with an added feature of emergency communication with a parent device. The device makes use of artificial intelligence to create a sensor network using an ultrasonic sensor, and a water sensor. The system includes a buzzer and a vibrator to alert the user of obstacles or sensed slippery surfaces, enabling the user in avoiding the hazards. The system incorporates GSM and GPS modules to permit communication between the device user and their caretakers and transmit the coordinates of the user in the form of a text message. This device is innovative and smart as it updates the visually impaired caretaker every two hours with his/her coordinates. The device is designed from off-the-shelf and light components making it light, handy, and user-friendly. Overall, the system aims to provide a low-cost and efficient navigation system/device which gives a sense of artificial vision by providing real-time environment information about the scenario of static and dynamic environments around them and tracking in real-time. The system includes an emergency switch to be used to alert a parent or caretaker.